SAT0521 Increasing physical activity in older people with pain. preliminary results of the ipopp pilot trial. (15th June 2017) - McBeth, J; Nicholls, E; Healey, E; Foster, NE; Hay, EM; Pincus, T; Dent, S; Chew-Graham, CA; Hartshorne, L; Jinks, C; ,
Abstract : Background: Chronic (≥3 months) pain is associated with physical inactivity in older (≥65 years) people. Walking is an acceptable form of physical activity with health benefits. We have developed Increasing Physical Activity in Older People with Pain (iPOPP), a brief intervention to increase walking. Objectives: To assess the acceptability and credibility of iPOPP, and to test the feasibility of trial processes, in a pilot randomised controlled trial. Methods: Eligible responders to a screening questionnaire (≥65 years; consulted their general practitioner for chronic pain; Chronic Pain Grade score ≥2) collected 7-day accelerometer data before randomisation and at the end of follow-up. Participants were randomised to one of Usual primary care; Pedometer, walking diary, pain toolkit (written pain management information); or iPOPP comprising week 1 face-to-face Health Care Assistant (HCA) consultation to develop a walking action plan, pedometer, walking diary, pain toolkit, discussion of walking behaviour and barriers, goal setting; week 2 follow up face-to-face or telephone (participant preferred) HCA consultation to review progress and goals, relapse prevention strategies; weeks 3–10 weekly motivational prompts (participant preferred postcard, email or text). A follow-up questionnaire was sent 12 weeks post-randomisation. Success criteria were: 7% of those screened would be eligible, return an accelerometer and be randomised; follow-up rates ≥75% of those randomised; ≥50% of those in iPOPP would complete week 1 and 2 intervention sessions; and a median score of ≥5/10 across a four-item intervention acceptability and credibility questionnaire. Results are number (%) or median (inter quartile range (IQR)). Results: Of 2326 people mailed, 1256 (54%) responded and 695 (30%) were eligible. After mailing study information to 425 eligible participants, 161 (38%) agreed to participate, 159 (12% of those mailed) returned an accelerometer and were randomised, 7 withdrew, and 136 (86%) returned a follow-up questionnaire. Of those randomised to iPOPP 82% completed week 1 and 2 intervention sessions; 32% had a face-to-face week 2 follow-up; 48% preferred postcard motivational prompts, 10% email, 22% text, and 20% had no preference. Median (IQR) acceptability and credibility scores were: "how logical is treatment?" 8 (3, 9.8), "confidence in treatment success" 5.5 (3, 8), "would recommend treatment to friend" 7 (3.3, 9), and "treatment would be successful for another pain problem" 5 (3, 7.8). 152 participants were mailed a follow-up accelerometer and 144 (95%) were returned. 147 (91%) baseline and 117 (81%) follow-up accelerometers had useable data. Conclusions: These data demonstrate the acceptability and credibility of the iPOPP intervention, and the feasibility of proposed trial processes. The effectiveness of iPOPP compared with usual care will be tested in a future main trial. Acknowledgements: Funded by Arthritis Research UK (grant reference 20608). ELH, CJ, and CCG are part funded by the NIHR Collaborations for Leadership in Applied Health Research and Care West Midlands. The views expressed in this paper are those of the author(s) and not necessarily those of the NHS, the NIHR, or the Department of Health. Disclosure of Interest: None declared